Configurations of Management Agreements in Hospitality Industry: Adaptations to Remuneration, Termination and Loss Compensation due to Uncertainty - Natalie Audrey Balch (Journal of Applied Leadership and Management, 2014)
Research questions: How are management agreements in the German hotel market configured as reaction to the growing uncertainty? Which adaptations are made to management agreements in Germany according to their uncertainty reducing effect? Is a higher level of flexibility negotiated into management agreements, in order to encounter uncertainty? Methods: Semi-structured expert interviews, forming a cross section of the target group being involved in the negotiation of management agreements, and giving insights about the driving forces and trends of the contract configuration.~ Results: Agreements are flexibilised in the area of remuneration and termination, whereby safeguarding is predominant in the areas of loss compensation. Negotiation power has a higher influence on the contract configuration than uncertainty issues.
Keywords: 650